Levonorgestrel intrauterine device in uterine leiomyomatosis-related hypermenorrhea - Tang, Luis (2015)
Objectives: To determine benefits of levonorgestrel intrauterine device (IUD) in uterine leiomyomatosis associated with hypermenorrhea. Design: Descriptive, retrospective study. Participants: Women with uterine leyomiomatosis and hypermenorrhea. Interventions: Levonorgestrel IUD was applied to 15 patients with uterine leiomyomatosis and hypermenorrhea as an alternative to usual surgical treatment. Patients with 2 to 5 cm average diameter leiomyomas not localized within the cavity were included, at most 4 in number, and followed for 12 months. Main outcome measures: Reduction of both leiomyoma size and menstrual volume. Results: One  patient expelled the IUD at 3 months from insertion. In 8 of the remaining 14 (57,1%) there was reduction of the leiomyoma size between 25 and 50% in relation to the original size; in 5 patients (35,7%) the size remained the same and in one (7,1%) it grew. Menstrual volume decreased statistically significant in 85,7% (12 of the 14 patients) including amenorrhea in two. Only one patient (7,1%) reported increase in menstrual volume. Conclusions: The study group was small but may serve for considering levonorgestrel IUD as an alternative to surgical treatment in patients with leiomyomata associated to hypermenorrhea.